Survival of Methanogenic Archaea from Siberian Permafrost under Simulated Martian Thermal Conditions - Morozova, Daria; Möhlmann, D.; Wagner, Dirk (Origins of Life and Evolution of Biospheres, 2007)
Since ESA mission Mars Express determined water on Mars, a fundamental requirement for life, as well as the presence of CH4 in the Martian atmosphere, which could only have originated from active volcanism or from biological sources, it is obviously that microbial life could still exist on Mars, for example in the form of subsurface lithoautotrophic ecosystems, which are also exist in permafrost regions on Earth. Present work deals with the resistance investigation of methanogenic archaea from Siberian permafrost complementary to the already well-studied methanogens from non-permafrost habitats under simulated Martian conditions. The methanogenic archaea in pure cultures as well as in permafrost samples represent higher survival potential (up to 90 percent) than the referent organisms (0.3-5.8 percent) after 22 days of exposure to thermo-physical Martian conditions at low- and mid-latitudes. It is suggested that methanogens from terrestrial permafrost seem to be more resistant against Martian conditions and could be used as a prime candidates for the search for extraterrestrial life.